ผลของชนิดของอิมัลซิไฟเออร์ต่อคุณลักษณะทางกายภาพของเบต้าแคโรทีนนาโนอิมัลชัน - ศรีรัตนโชติ เกศินี; พันพิพัฒน์ วรวรรณ; ชัยจันทร์ มนัส; หนิสอ หมุดตอเล็บ (Thai Journal of Science and Technology, 2019)
Abstract Preparation of β-carotene in nanoemulsion is one of an effective means to improve β-carotene bioactivity and bioavailability. The aim of this study was to investigate the effect of emulsifier types on the physical properties of β-carotene nanoemulsion. To prepare the nanoemulsion, β-carotene was dissolved in rice bran oil (45% w/w) at 60°C under nitrogen gas for 1 h with oil volume fraction of 0.1. Different emulsifiers and their mixtures (3 %) were employed for nanoemulsion fabrication including Tween 80, Span 80, lecithin, β-lactoglobulin (β-Lg), whey protein isolate (WPI), lecithin+Tween 80, lecithin+WPI and Tween 80+Span 80. Emulsion was prepared using a bath sonicator for 10 min followed by a probe sonicator (40 watt and 25 % amplitude) for 10 min. The median droplet size diameter, polydispersity index (PDI), zeta potential, emulsion activity index (EAI), emulsion stability index (ESI) and microstructure of corresponded emulsions were immediately analyzed. The smallest mean particle size diameter (263 nm) was observed in nanoemulsion made by Tween 80 mixed with Span 80. This mixed emulsifier rendered the nanoemulsion with the lowest PDI and distributed more uniform when observed with confocal scanning light microscopy. All emulsions showed the zeta potential lower than -30 mV indicating high stability of these emulsions. The EAI and ESI were higher in proteins-stabilized emulsions. From the results, the β-carotene nanoemulsion was successfully produced by the aid of Tween 80 mixed with Span 80 as an active emulsifier mixture, which exhibited the mean particle size diameter of less than 500 nm. Keywords: β-carotene; emulsifier; nanoemulsion; physical property